Analisis Unsur Budaya Jawa Wayang pada Cerpen Semar Tresno - Aisyah Novy Prabawati; Imam Baihaqi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2026)
Culture is all the results of the work, creativity, and feelings of society so that all forms of a community group are forms of culture which then in one society creates many cultural aspects. Based on the elements that form the culture, this article will discuss art which is part of culture and a means used to express the sense of beauty from within the human soul and has other functions. The descriptive qualitative analytical approach method is a method used to obtain in-depth data, data that contains meaning and can significantly influence the substance of the research. In the short story entitled